The political economy of financial regulation / edited by Emilios Avgouleas, David C. Donald. - Avgouleas, Emilios; Donald, David C., 1958- (International corporate law and financial market regulation., 2019)
This collection of cutting-edge scholarship examines the law and policy of financial regulation using a combination of conceptual analysis and strong empirical research. The book's authors range from global leaders to rising stars in the field, all of whom shed light on complex questions of financial sector regulation theory and practice in key economies ranging from the EU to China. Key topics include the role of law in constituting financial markets, the efficiency of markets, the role of interest groups in shaping financial regulation, the interdependence and interactions of international financial regulation with international trade and monetary regimes, and problems of regulation in state capitalism economies. This exciting volume opens the road for further enrichment of the academic and policy-making dialogue on financial regulation and regulatory practice, and reflects new trends in legal and social-science scholarship.